AKOMODASI KOMUNIKASI ANTARBUDAYA PADA MAHASISWA SUMATRA UTARA DI UNIVERSITAS NEGERI GORONTALO - SUMARJO, SUMARJO; Siallagan, Fernandes; Tamu, Yowan (Program Studi Ilmu Komunikasi FISIP UM Buton, 2024)
The research background rested on disclosing the adaptation of North Sumatra students in Gorontalo in the stage of communication accommodation. The aimwas to reveal the stages of accommodation chosen by North Sumatra students when adjusting themselves in Gorontalo. This research was conducted based on the qualitative phenomenological method, which describes the communication accommodation of North Sumatra students. The communication theory used was communication accommodation, which consists of three stages: Convergence, Diversity, and over- accommodation. The results showed that the North Sumatra students tended to accommodate the convergence stage, indicating an interest in harmonizing communication. However, some chose the Divergence stage, wherethey showed significant differences, such as intentionally not adapting, especiallyin language. Additionally, some North Sumatra students in the over-accommodation stage excessively used their native North Sumatra language in interactions. Keywords: Communication Accommodation, North Sumatra Students